Private and public risk sharing in the euro area - Jacopo Cimadomo; Oana Furtuna; Massimo Giuliodori (European Central Bank (ECB), 2018)
This paper investigates the contribution of private and public channels for consumption risk sharing in the EMU over the period 1999-2015. In particular, we explore the role of financial integration versus international financial assistance for private consumption smoothing in this set of countries. In addition, we present a time-varying test which allows estimating how risk sharing has evolved since the start of the EMU, and in particular during the recent crisis. Our results suggest that, whereas in the early years of the EMU only about 40% of country-specific output shocks were smoothed, in the aftermath of the euro zone's sovereign debt crisis about 65% of these shocks were absorbed, therefore reducing consumption growth differentials across countries. This progressive improvement of the shock-absorption capacity is due to a higher financial integration, but also to the activation of the European Financial Stability Facility (EFSF) and the European Stability Mechanism (ESM) channelling official loans to distressed euro zone economies. We also show that cross-border holdings of equities and debt seem to be more effective than cross-border bank loans in isolating households from country-specific shocks, therefore contributing to consumption smoothing.
Keywords: C23; E62; G11; G15; 330; risk sharing; time-variation; financial integration; international financial assistance